2005
DOI: 10.1016/j.ejcts.2004.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Patient-prosthesis mismatch in aortic valve replacement: really tolerable?

Abstract: In patients with severe ventricular hypertrophy it may be important to elude patient-prosthesis mismatch to avoid a significant increase in mortality and improve ventricular mass regression. Mismatch may be tolerable in those patients with lesser degree of hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…6 This focus in prosthesis development is further fueled by the finding that PPM (prosthesis considered too small for the patient, introducing functional obstruction to flow) increases mortality after AVR, 24 and impairs LV mass regression after both SAVR and TAVR. 17,25 This complicates the finding that LV mass regression is greater after SAVR given the significantly lower rate of PPM in TAVR and higher survival after CoreValve implantation compared to SAVR. 9 The majority of LV mass regression after AVR (10% to 30%) is complete by 1 year, but this process of reverse remodeling continues for several years after AVR, 26,27 despite the presence of a constant, albeit smaller, pressure gradient with the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This focus in prosthesis development is further fueled by the finding that PPM (prosthesis considered too small for the patient, introducing functional obstruction to flow) increases mortality after AVR, 24 and impairs LV mass regression after both SAVR and TAVR. 17,25 This complicates the finding that LV mass regression is greater after SAVR given the significantly lower rate of PPM in TAVR and higher survival after CoreValve implantation compared to SAVR. 9 The majority of LV mass regression after AVR (10% to 30%) is complete by 1 year, but this process of reverse remodeling continues for several years after AVR, 26,27 despite the presence of a constant, albeit smaller, pressure gradient with the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…9 The majority of LV mass regression after AVR (10% to 30%) is complete by 1 year, but this process of reverse remodeling continues for several years after AVR, 26,27 despite the presence of a constant, albeit smaller, pressure gradient with the prosthesis. Available data, although limited, suggest that residual LV hypertrophy has a negative impact on long-term survival after AVR in patients with severe aortic stenosis, 25,28 but other findings indicate that only a high preoperative LV mass, and not the extent of LV mass regression, determine clinical outcomes. 29 Greater early regression of LV mass index seen at 1 month post-TAVR with the SAPIEN valve (Edwards Lifesciences, Irvine, CA, USA) was associated with significantly decreased re-hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in increasing number of patients with PPM after AVR. Some previous studies have reported that the risk factors for AVR patients with aortic stenosis developing PPM postoperatively are female gender and advanced age [2][3][4]10 . Aortic annular enlargement procedures should achieve the optimal measurements to prevent PPM, but these procedures lengthen the cardiopulmonary bypass and cross clamp times, increasing the surgical risks.…”
Section: The Significance Of Ieoamentioning
confidence: 99%
“…However, LV workload remains high after AVR due to persistent PPM, which may increase LVM again during the follow-up period. On the other hand, many studies have been reported that mild to moderate PPM appears to have little or no effect on postoperative recovery of cardiac function, late cardiac events and survival [5][6][7][8][9][10][11][12] . Such degree of PPM may be acceptable in not only elderly patients but also younger patients 7 .…”
Section: The Significance Of Ieoamentioning
confidence: 99%
See 1 more Smart Citation